2018
DOI: 10.3390/nu10060790
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Requirements of Lung Transplant Recipients: Challenges and Considerations

Abstract: An optimal nutritional status is associated with better post-transplant outcomes and survival. Post-lung transplant nutrition management is however particularly challenging as lung recipients represent a very heterogeneous group of patients in terms of age, underlying diseases, weight status and presence of comorbidities. Furthermore, the post-transplant period encompasses several stages characterized by physiological and pathophysiological changes that affect nutritional status of patients and necessitate tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 101 publications
(155 reference statements)
2
18
1
Order By: Relevance
“…To our knowledge, there are no standardized guidelines to combat malnutrition in chronic lung disease, but general recommendations aim to offset weight loss through nutritional recommendations with the goal of preventing any further weight loss. 44 - 46 We observed that 86% of LTx candidates were able to maintain or gain weight (≥5%) during the pretransplant period with nutritional counseling, but the change in weight on average was minimal as in other studies. 24 Given that nutritional counseling is standard of care at our center, we are unable to evaluate the degree of weight loss that may have ensued without nutritional care.…”
Section: Discussionsupporting
confidence: 45%
“…To our knowledge, there are no standardized guidelines to combat malnutrition in chronic lung disease, but general recommendations aim to offset weight loss through nutritional recommendations with the goal of preventing any further weight loss. 44 - 46 We observed that 86% of LTx candidates were able to maintain or gain weight (≥5%) during the pretransplant period with nutritional counseling, but the change in weight on average was minimal as in other studies. 24 Given that nutritional counseling is standard of care at our center, we are unable to evaluate the degree of weight loss that may have ensued without nutritional care.…”
Section: Discussionsupporting
confidence: 45%
“…90 Those with BMI >30 kg/m 2 and obese patients who were unable to lose weight prior to transplant had worse outcomes. 91 Posttransplant nutritional management challenges in these highly catabolic patients were described by Jomphe et al 92 Active casual alcohol use prevalence was about 1 in 3 prior to transplantation and was associated with a 300% increase in mechanical ventilation time and ICU stay and a 150% increase in hospital stay, but mortality and graft function outcomes were not statistically different. 93 E-cigarette use increased in this population.…”
Section: Lung Transplantationmentioning
confidence: 98%
“…Given that this area of medical science is young and developing, expert opinion has been the basis of much of the criteria available [4].…”
Section: Lung Transplant Candidate Selectionmentioning
confidence: 99%